Nutritional Composition and Antioxidant Activity of Freshwater Lobster in Malaysia: A Short Review - TENGKU ZAINAL ABIDIN, TENGKU ZARITH HAZLIN; MAT ALI, NURIN NAJMINA; ABU BAKAR, FAZLEEN IZZANY; AHMAD BAKRI, FAIZNUR AIN; ABU BAKAR, MOHD FADZELLY; MALIK, NUR HAFIZAH; ZAINAL ABIDIN, MUNIRA (2023)
Freshwater lobster or scientifically known as Cherax quaricarinatus is a non-native species from Northern Australia and resided in Malaysia in the early 1980s. Out of species in freshwater crayfish groups, the red claw is the sole tropical species and has received much appreciation for being a top option for aquaculture. Thus, this study reviews C. quadricarinatus in Johor, Malaysia in terms of its origin, influence in agriculture, nutritional composition, as well as the antioxidant activity. It can be concluded that the consumption of crayfish lobster offers many health benefits due to its high antioxidant content and nutritional value.